Welfare impacts of climate-smart agriculture in Ghana: does row planting and drought-tolerant maize varieties matter? - Martey, E.; Etwire, P.M.; Abdoulaye, Tahirou (Elsevier, 2020)
This study provides new evidence of the impact of climate-smart agriculture (CSA) – row planting and drought-tolerant maize varieties - on farm and welfare outcomes by estimating a multinomial endogenous switching regression model that corrects for selection bias and farmer heterogeneity in CSA choice. Application of our model to panel observations of 438 households in Ghana show that adoption of CSA increases both yield and intensity of maize commercialization but negatively affect own consumption. Specifically, the magnitude of the impact is relatively higher for adopters of row planting relative to adopters of drought-tolerant maize seeds. These results suggest the need for development practitioners to increase awareness and emphasize the importance of row planting as a key component of climate-smart agriculture.